Systematic Review of the Genetics of Sudden Unexpected Death in Epilepsy: Potential Overlap With Sudden Cardiac Death and Arrhythmia‐Related Genes - Chahal, C. Anwar A.; Salloum, Mohammad N.; Alahdab, Fares; Gottwald, Joseph A.; Tester, David J.; Anwer, Lucman A.; So, Elson L.; Murad, Mohammad Hassan; St Louis, Erik K.; Ackerman, Michael J.; Somers, Virend K. (Journal of the American Heart Association, 2020)
Background Sudden unexpected death in epilepsy (SUDEP) is the leading cause of epilepsy-related death. SUDEP shares many features with sudden cardiac death and sudden unexplained death in the young and may have a similar genetic contribution. We aim to systematically review the literature on the genetics of SUDEP. Methods and Results PubMed, MEDLINE Epub Ahead of Print, Ovid Medline In-Process & Other Non-Indexed Citations, MEDLINE, EMBASE, Cochrane Database of Systematic Reviews, and Scopus were searched through April 4, 2017. English language human studies analyzing SUDEP for known sudden death, ion channel and arrhythmia-related pathogenic variants, novel variant discovery, and copy number variant analyses were included. Aggregate descriptive statistics were generated; data were insufficient for meta-analysis. A total of 8 studies with 161 unique individuals were included; mean was age 29.0 (±SD 14.2) years; 61% males; ECG data were reported in 7.5% of cases; 50.7% were found prone and 58% of deaths were nocturnal. Cause included all types of epilepsy. Antemortem diagnosis of Dravet syndrome and autism (with duplication of chromosome 15) was associated with 11% and 9% of cases. The most frequently detected known pathogenic variants at postmortem were in Na and K ion channel subunits, as were novel potentially pathogenic variants (11%). Overall, the majority of variants were of unknown significance. Analysis of copy number variant was insignificant. Conclusions SUDEP case adjudication and evaluation remains limited largely because of crucial missing data such as ECGs. The most frequent pathogenic/likely pathogenic variants identified by molecular autopsy are in ion channel or arrhythmia-related genes, with an ≈11% discovery rate. Comprehensive postmortem examination should include examination of the heart and brain by specialized pathologists and blood storage.